LACTOFERIN IN THE PROBLEM OF ANTI-INFECTIOUS PROTECTION OF BABIES IN THEIR FIRST YEAR OF LIVING - P. E. Sadchikov; I. G. Goldman; L. S. Namazova-Baranova; G. V. Yatsik; T. E. Borovik; A. D. Chernousov; А. I. Romanchenko; E. R. Sadchikova; O. L. Lukoyanova; N. G. Zvonkova; I. A. Belyaeva (Педиатрическая фармакология)
The author  summarizes  the  results  of research  of the  antibacterial,  antiviral  and  antifungal  properties  of multifunctional  human protein  — lactoferrin,  in order  to determine  the prospects  for its use in the prevention  and  treatment  of infectious  diseases  of children in their first year of life. The mechanisms of anti-infectious effect of this protein with breastfed children have been described. Basic differences between human lactoferrin and cattle lactoferrin have been shown. Biotechnology of obtaining recombinant human lactoferrin from the milk of genetically engineered dairy animals (goat-producers) has been described. According to the studies, both by physical and chemical parameters and biological activity, human lactoferrin, obtained from milk-producing  goats, corresponds to its natural counterpart.